Matching‐adjusted indirect comparisons of oral rimegepant versus placebo, erenumab, and galcanezumab examining monthly migraine days and health‐related quality of life in the treatment of migraine. Issue 6 (22nd May 2021) - Popoff, Evan; Johnston, Karissa; Croop, Robert; Thiry, Alexandra; Harris, Linda; Powell, Lauren; Coric, Vladimir; L'Italien, Gilbert; Moren, James
Abstract: Objective: Rimegepant is an orally administered small‐molecule calcitonin gene‐related peptide (CGRP) receptor antagonist, with demonstrated efficacy in the acute treatment of migraine. Recent estimates from a single‐arm trial (BHV3000‐201) have also shown evidence of long‐term preventive effects in monthly migraine days (MMDs) and health‐related quality of life (HRQoL). This study aimed to compare MMDs and HRQoL data for oral rimegepant to those obtained in placebo‐controlled trials for injectable anti‐CGRP monoclonal antibodies (mAbs) galcanezumab and erenumab. Methods: Matching‐adjusted indirect comparisons (MAICs) were conducted using rimegepant subject‐level data and published aggregate‐level results from mAb trials. Rimegepant baseline characteristics were matched to the pooled subject characteristics from EVOLVE‐I/II (galcanezumab vs. placebo; n  = 1773) and STRIVE (ereumab vs. placebo; n  = 955) by reweighting the rimegepant subjects to more closely match the distributions observed in these trials. To align with inclusion criteria of the mAb trials, only the subset of rimegepant subjects with a history of 4–14 MMDs were included ( n  = 257). Weighted mean differences were used to calculate adjusted change in MMDs, Migraine Disability Assessment Test (MIDAS) score, and Migraine‐Specific Quality of Life Questionnaire version 2 (MSQv2) scores from baseline to week 12. Results: When matched to the EVOLVE trials, rimegepant was superior to placebo with a mean difference in MMD change from baseline [95% confidence interval] of −1.16 [−1.80, −0.52] and was not statistically significantly different from galcanezumab 0.59 [−0.13, 1.32]. When matched to the STRIVE trial, rimegepant was superior to placebo −1.59 [−2.15, −1.03] and was not statistically significantly different from erenumab −0.06 [−0.61, 0.50]. Rimegepant showed superior MIDAS and MSQv2 results compared with placebo in both EVOLVE trials and in the STRIVE trial, no statistically significant differences from galcanezumab and erenumab regarding MIDAS, and favorable results compared with erenumab across all MSQv2 domains, while being generally similar to galcanezumab across all MSQv2 domains. Conclusions: When adjustments were made to reflect baseline characteristics in published literature, supporting data from BHV3000‐201 suggest that rimegepant every other day is an effective therapy in reducing disability and MMDs and enhancing migraine‐specific HRQoL. These data support the preventive benefit observed in randomized trials of rimegepant and further validate its efficacy for both acute and preventive treatment of migraine.